What does anticipated monetary policy do? - Stefania D'Amico; Thomas B. King (Federal Reserve Bank of Chicago, 2015)
Forward rate guidance, which has been used with increasing regularity by monetary policymakers, relies on the manipulation of expectations of future short-term interest rates. We identify shocks to these expectations at short and long horizons since the early 1980s and examine their effects on contemporaneous macroeconomic outcomes. Our identification uses sign restrictions on survey forecasts incorporated in a structural VAR model to isolate expected deviations from the monetary- policy rule. We find that expectations of future policy easing that materialize over the subsequent four quarters - similar to those generated by credible forward guidance - .have immediate and persistent stimulative effects on output, inflation, and employment. The effects are larger than those produced by an identical shift in the policy path that is not anticipated. Our results are broadly consistent with the mechanism underlying forward guidance in New Keynesian models, but they suggest that those models overstate the persistence of the inflation response. Further, we find that changes in short-rate expectations farther in the future have weaker macroeconomic effects, the opposite of what most New Keynesian models predict.
Keywords: 330